2001
DOI: 10.1161/hh2401.101907
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Angiotensin II-Induced Increase of Chloride/Bicarbonate Exchange in the Myocardium

Abstract: Abstract-Plasma membrane anion exchangers (AEs) regulate myocardial intracellular pH (pH i ) by Na ϩ -independent Cl Ϫ /HCO 3 Ϫ exchange. Angiotensin II (Ang II) activates protein kinase C (PKC) and increases anion exchange activity in the myocardium. Elevated anion exchange activity has been proposed to contribute to the development of cardiac hypertrophy. Our Northern blots showed that adult rat heart expresses AE1, AE2, AE3fl, and AE3c. Activity of each AE isoform was individually measured by following chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 60 publications
(54 reference statements)
3
54
0
7
Order By: Relevance
“…A previous study by our group showed that AE3 is closely linked with the inhibitory effects of SQS on sI/R-induced elevation of [Cl -] i (9). Of note, Alvarez et al (29) showed that AE3 is the PKC-sensitive anion exchange protein of the heart, and that the PKCε-dependent phosphorylation of serine 67 on AE3 can cause an increase in anion transport. Therefore, it may be speculated that SQS inhibits sI/R-induced elevation of [Cl -] i and induces cardioprotection through activation of the PKCε pathway and consequent PKCε-dependent phosphorylation of serine 67 on AE3.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study by our group showed that AE3 is closely linked with the inhibitory effects of SQS on sI/R-induced elevation of [Cl -] i (9). Of note, Alvarez et al (29) showed that AE3 is the PKC-sensitive anion exchange protein of the heart, and that the PKCε-dependent phosphorylation of serine 67 on AE3 can cause an increase in anion transport. Therefore, it may be speculated that SQS inhibits sI/R-induced elevation of [Cl -] i and induces cardioprotection through activation of the PKCε pathway and consequent PKCε-dependent phosphorylation of serine 67 on AE3.…”
Section: Discussionmentioning
confidence: 78%
“…On one hand, it has been shown by some authors of the present study that exogenous applied Ang II induces AE3 activation by PKC-⑀-dependent phosphorylation of the AE3fl isoform on Ser67. 41 Myocardial stretch probably shares the same pathway. On the other hand, Moor and Fliegel 42 demonstrated that ET induces NHE-1 stimulation through the 42/44 mitogen-activated protein kinase and p90, which are both known as downstream effectors from PKC.…”
Section: Twitch Relaxation Indexesmentioning
confidence: 99%
“…Perhaps the AE3 isoforms, and particularly the AE3fl, are the ones linked to PKC-dependent activation. In addition to be PKC-⑀-dependent phosphorylated by Ang II, 41 the AE3fl isoform is upregulated in the hypertrophied myocardium of the SHR where pH i is compensated in spite of the enhanced NHE-1 activity. 17…”
Section: Twitch Relaxation Indexesmentioning
confidence: 99%
“…54 Involvement of AE3 in cardiac hypertrophy is supported by the observation that it is the only family member that can be activated by protein kinase C (PKC), which is the kinase implicated in hypertrophic pathways. 55 AE3 is also expressed in the retina, where it may regulate pH and HCO 3 -levels since the retina is the most energy-utilizing tissue of the body, with an associated high HCO 3 -load. In the retina there is differential expression of AE3c and AE3fl in the Müller glial cell or horizontal cell layers, and there is also differential expression at different developmental stages.…”
Section: Introductionmentioning
confidence: 99%